FLOWABILITY OF NANOPARTICLES OF CALCIUM HYDROXIDE PALIMANAN IN DENTINAL TUBULE - Sidiqa, Atia Nurul; Muqdas, Faza Annisa; Artilia, Ira; Zakaria, Myrna Nurlatifah; Joni, I Made; Maskoen, Ani Melani (Faculty of Dentistry, Universitas Islam Sultan Agung, 2024)
Background: Intracanal medicaments Ca(OH)₂ must have the ability to contact directly with bacteria adhering to the dentinal tubules. However, the narrow and complex shape of the root canal makes it difficult for Ca(OH)2 to penetrate the root canal apically. This research aimed to assess the flowability of nanoparticle Ca(OH)₂ Palimanan by quantifying the penetration of the coronal, middle, and apical thirds of the root canal.Methods: This research comprised two distinct groups: one group included nanoparticles of Ca(OH)₂ Palimanan, while the other consisted of conventional Ca(OH)₂. The paste was then applied to standardized root canals (n=3 per group) with 5 times measurements for each sample. All samples were then incubated at 37oC, 100% humidity. The flowability of the root canals was measured using scanning electron microscopy (SEM) on day 14. The data was analyzed using ANOVA and a post-hoc t-test, with a significance level of p<0.05.Results: The use of Ca(OH)₂ Palimanan has been found to be more effective in reaching deeper into the dentinal tubules of the root canal, particularly in the coronal, middle, and apical areas, compared to traditional Ca(OH)₂. This occurs because the particle size of Ca(OH)₂ Palimanan is smaller with a more rounded shape than conventional Ca(OH)₂ so that it to flow into narrow and complex areas, especially in the apical root canals.Conclusion: Nanoparticle Ca(OH)₂ Palimanan flow deeper than conventional Ca(OH)₂